Jesuits in India: Vision and Challenges - Nellissery, Raju (Journal of Dharma, 2008)
Delio De Mendonca, Jesuits in India: Vision and Challenges, Gujarat, India: Gujarat Sahitya Prakash, 2003, pages xxiv + 380, ISBN: 818788678-1.